Generation of new rice germplasms with low amylose content by CRISPR/CAS9-targeted mutagenesis of the FLOURY ENDOSPERM 2 gene - Song, Xiaohong; Chen, Zhihui; Du, Xi; Li, Bin; Fei, Yunyan; Tao, Yajun; Wang, Fangquan; Xu, Yang; Li, Wenqi; Wang, Jun; Liang, Guohua; Zhou, Yong; et al. (Frontiers in Plant Science, 2023)
FLOURY ENDOSPERM 2 (FLO2), encoding a tetratricopeptide repeat domain (TPR)-containing protein located in the nucleus, is considered to be a regulatory protein that controls the biosynthesis of seed storage substances. The diversity of flo2 allele is attributable for the variations in grain appearance, amylose content (AC), and physicochemical properties, influencing the eating and cooking quality (ECQ) of rice. In this study, we used CRISPR/Cas9 to introduce loss-of-function mutations into the FLOURY ENDOSPERM 2 gene in Suken118 (SK118), a widely cultivated elite japonica rice variety in Jiangsu, China. Physiochemical analyses of the flo2 mutants were congruent with previous studies, exhibiting lowered AC and viscosity, risen gel consistency (GC) and gelatinization temperature (GT) values, which were all instrumental to the improvement of ECQ. However, the wrinkled opaque appearance and the decrease in grain width, grain thickness and grain weight imply trade-offs in grain yield. Despite the ex-ante estimation for low yielding, the superior ECQ in these novel genotypes generated by using genome editing approach may have the potential for formulating high value specialty food.